Influence of Water Table Depth on Pore Water Chemistry and Trihalomethane Formation Potential in Peatlands. (1st February 2016) - Gough, Rachel; Holliman, Peter J.; Fenner, Nathalie; Peacock, Mike; Freeman, Christopher
ABSTRACT: : Drained peatland catchments are reported to produce more colored, dissolved organic carbon (DOC)‐rich water, presenting problems for potable water treatment. The blocking of peatland drainage ditches to restore the water table is increasingly being considered as a strategy to address this deterioration in water quality. However, the effect of ditch blocking on the potential of DOC to form trihalomethanes (THMs) has not been assessed. In this study, the effect of peat rewetting on pore water DOC concentration and characteristics (including THM formation potential [THMFP]) was assessed over 12 months using peat cores collected from two drained peatland sites. The data show little evidence of differences in DOC concentration or characteristics between the different treatments. The absence of any difference in the THMFP of pore water between treatments suggests that, in the short term at least, ditch blocking may not have an effect on the THMFP of waters draining peatland catchments.